Production of ferric ammonium sulfate (FAS) dodecahydrate from pyrite (FeS2) - Wilson Kobal; Rachel A. Pepper; Jose A. Alarco; Wayde Martens; Sara J. Couperthwaite (Environmental Challenges)
Pyrite is a waste material typically formed after the extraction of valuable metals from numerous mineral processing circuits, such as copper, gold, and lead. Leaching of pyrite at abandoned mine sites presents significant environmental risks due to the formation of acid mine drainage (AMD). The primary aim of this work was to investigate the recovery of Fe and S from pyrite materials, using acid leaching methods, to produce ferric ammonium sulfate dodecahydrate (FAS; FeNH4(SO4)2·12H2O), which has applications in water treatment, dye industries and metal fabrication. As pyrite samples contain various minerals, the acid leachates contained impurities, such as Al, Ca, Mn, and therefore optimisation studies to produce FAS from pyrite leachates was undertaken based on type of acid, concentration and residence time for leach and crystallisation stages. FAS crystallisation tests were conducted using solutions that were obtained from pyrite leached with nitric acid of 1–5 M, using a crystallisation time of 30 mins, agitation at 400 rpm and at temperatures < 10 °C. Crystals were observed to start forming within 5 mins at this temperature range. This study developed a pathway for FAS synthesis from iron-rich mining waste which occurs at mild conditions and is more direct than traditional FAS synthesis methods.